MINAT SISWA SEKOLAH DASAR TERHADAP BOLAVOLI MINI (SURVEI PADA SISWA KELAS V SDN SE-KOTA BLITAR) - RAHADI, SATRIA (Jurnal Prestasi Olahraga, 2013)
The introduction of mini volleyball in schools is expected can attract the interest of students and make mini volleyball be known by all of students, because without high interest, it can be difficult to make it familiar especially for elementary school?s student. Every parents have a dream that their children can be success and get all of they want in their future, including for sport achievement. The purpose of this study was to find elementary school students? interest towards mini volleyball.Thus, the purpose The main targets of this research were the student and the school. The method which was used in this research was descriptive quantitative method and the data collection was done by filling questionaries? to elementary school students. There are twenty nine of elementary schools in Blitar. The results of this study show that the students have an opinion that mini volleyball is a fun sport. So, from the data, it shows that the interest of mini volleyball is influenced by several factors, they are, the sense of fun on mini volleyball, the interest which comes from themselves and the explanation of the teachers which can determine the attitude of each students about mini volleyball. It can be concluded that in order to increase the interest of elementary school students about volleyball, it needs some supporting factors. So that, the interest of participating in volleyball can be increased and give the best achievement which can be proud.